Increased Leg Strength After Concurrent Aerobic and Resistance Exercise Training in Older Adults Is Augmented by a Whole Food-Based High Protein Diet Intervention - Timmons, James F.; Hone, Michelle; Cogan, Karl E.; Duffy, Orlaith; Egan, Brendan (Frontiers in Sports and Active Living, 2021)
Most studies in older adults have utilized powdered protein supplements or oral nutrition solutions as a source of additional dietary protein, but whole foods may provide a greater anabolic stimulus than protein isolated from food matrices. Therefore, the present study investigated a concurrent aerobic and resistance exercise training program in older adults, in the absence or presence of a high protein whole food-based dietary intervention, for effects on strength, physical function, and body composition. Community-dwelling older adults (n = 56; M/F, 28/28; age, 69.3 ± 4.0 years; BMI, 26.6 ± 3.7 kg m−2) participated in a 12-week intervention after randomization to either nutrition only (NUTR; n = 16), exercise only (EX, n = 19), or nutrition plus exercise (NUTR + EX, n = 21) groups. NUTR and NUTR + EX followed a dietary intervention targeting an increase in protein-rich meals at breakfast, lunch, and dinner. Exercise training in EX and NUTR + EX consisted of 24 min sessions of concurrent aerobic and resistance exercise performed three times per week. Daily protein intake increased in NUTR and NUTR + EX, but not EX. The increase in 1RM leg press strength was greater (Interaction effect, P = 0.012) in NUTR + EX [29.6 (18.1, 41.0) kg] than increases observed in NUTR [11.1 (−1.3, 23.6) kg] and EX [12.3 (0.9, 23.8) kg]. The increase in 1RM chest press strength was greater (interaction effect, P = 0.031) in NUTR + EX [6.3 (4.0, 8.6) kg] than the increase observed in NUTR [2.9 (0.3, 5.5) kg], but not EX [6.3 (3.9, 8.7) kg]. Hand-grip strength and sit-to-stand performance were each improved in all three groups, with no differences observed between groups (interaction effect, P = 0.382 and P = 0.671, respectively). An increase in percentage body fat was observed in NUTR, but not in EX or NUTR + EX (interaction effect, P = 0.018). No between-group differences were observed for change in lean body mass (interaction effect, P = 0.402). Concurrent aerobic and resistance exercise training improves strength and physical function in older adults, but combining this training with an increase in daily protein intake through whole foods may be advantageous to increase lower limb strength.